Memories ignored: the beginning of Maringa from the perspective of popular housing - Garcia, Tatiane Boisa [UNESP]; Souza Cordovil, Fabiola Castelo de (Univ Estadual Londrina, 2019)
Based on local historical formation, the present article analyzes the beginning of Maringa, emphasizing guiding principles and state actions in relation to popular housing during the structuring of the urban territory. It was tried to establish from a historiographic research a discourse that permeated by the trajectory of the state actions, of the involved agents, of the discourses, of the conflicts, of the orientations of the urbanistic legislations and of the results in the urban territory of Maringa from 1947 until 1964. The principles that guided the initial plan of Jorge de Macedo Vieira and later the actions of the municipal public power formalize in their urban structure an excluding genesis with initiatives disconnected from a public housing policy and that only responded to the real estate pressures and the ideal of a beautiful, modern and absent city of ills. The official historiography of the beginning of Maringa scarcely exposes the reality of the low-income population, however, since its origin, the city was overflowing with social problems and various precarious and extreme poverty centers were developed systematically ignored in local urban history.
Keywords: History of housing; History of Maringa; Urban History; Social housing; Slums